2011
DOI: 10.1186/1472-698x-11-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing community perspectives of the community based education and service model at Makerere University, Uganda: a qualitative evaluation

Abstract: BackgroundCommunity partnerships are defined as groups working together with shared goals, responsibilities, and power to improve the community. There is growing evidence that these partnerships contribute to the success and sustainability of community-based education and service programs (COBES), facilitating change in community actions and attitudes. Makerere University College of Health Sciences (MakCHS) is forging itself as a transformational institution in Uganda and the region. The College is motivated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…Therefore, agreeing with Prose et al, [8] the possibility of a more timely course, which also promotes cultural competence, should be investigated. We agree with Mbalinda et al [6] that a translator, who could also aid cultural understanding, can be a valuable communica tion tool. Although an interpreter accompanied the participants in this study on their home visits, there was still a barrier in communication with the client.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, agreeing with Prose et al, [8] the possibility of a more timely course, which also promotes cultural competence, should be investigated. We agree with Mbalinda et al [6] that a translator, who could also aid cultural understanding, can be a valuable communica tion tool. Although an interpreter accompanied the participants in this study on their home visits, there was still a barrier in communication with the client.…”
Section: Discussionsupporting
confidence: 90%
“…[2,4,6] The students stated that being proficient in isiXhosa would have helped in HBR to minimise the verbal communication barrier. They reported that an introductory isiXhosa course in their 1st year seemed irrelevant to them at the time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theme revealed positive outcomes based on several factors, including collaborative partnership, impact to student learning, [12,36,[45][46][47][48][49][50] community academic partnership, [51,52] cultural competence, [6,41,42] faculty-student relationship [20] and access to funding and developing a relationship between the university and community. [6,8,36,53] Linda et al [8] used an interpretive existentialistphenomenological approach to describe a community-based education program.…”
Section: Theme 3: the Impact Of Community Nursing Education Programsmentioning
confidence: 99%